Efficacy of Using the Japanese Version of the Asthma Control Test for Determing the Level of Asthma Control in Clinical Settings - Takashi Hasegawa; Toshiyuki Koya; Takuro Sakagami; Hiroshi Kagamu; Hidenori Kawakami; Katsuhito Hara; Fumitoshi Yoshimine; Masaaki Arakawa; Fumitake Gejyo; Ichiei Narita; Eiichi Suzuki (Allergology International, 2012)
Background: The Asthma Control Test (ACT) is frequently used for the evaluation of asthma control in clinical care setting because it does not require the use of pulmonary function tests, which can be difficult for general practitioners to use. However, few large-scale studies have investigated the efficacy of the Japanese version ACT (J-ACT) in actual use during clinical care. Methods: The aim of this study was to analyze the efficacy of the J-ACT in a clinical care setting. Using data from a 2008 questionnaire survey including the J-ACT by the Niigata Asthma Treatment Study Group, we compared the ACT scores of 2233 patients with respect to multiple parameters, including the severity by Japanese Society of Allergology and the attack frequency. Using the definition of asthma control partially referred to Global Initiative for Asthma (GINA) guidelines from the survey data, the accuracy screening and determination of optimal ACT cutpoints were performed by retrospective analysis. Results: Cronbach's a for the J-ACT was 0.785. Patients with more severe asthma and more frequent asthma attacks had lower ACT scores than did patients with less severe, less frequent attacks. The optimal ACT cutpoints were 24 for the controlled asthma and 20 for the uncontrolled asthma. Conclusions: Our study, the first large-scale investigation of the efficacy of the J-ACT, determined that this evaluation tool is highly efficacious in establishing the level of asthma control. However, the determination of accurate cutpoints for the J-ACT will require more clear definitions of asthma control in future prospective studies.